2020
DOI: 10.1002/apj.2453
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pore size of monofilament woven filter cloth as supporting material for dynamic membrane filtration on performance using aerobic membrane bioreactor technology

Abstract: Dynamic membranes (DMs) defined as cake layer forms on a support material such as filter cloth have been of great interest in recent years. The usage of DMs can reduce the capital cost significantly and energy consumption during wastewater treatment by replacing the conventional membrane. The formation of an active dynamic cake layer is highly related to the retention of particles on the support material surface. In this study, different pore sizes of monofilament woven filter cloth made of polypropylene (PP; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…In COD and TDS removal, the PSf/PVP 0.35 membrane had the highest removal efficiency. It indicated that the pore size affected the removal process, where it was previously confirmed that the PSf/PVP 0.35 membrane had the lowest porosity compared to other membranes [ 55 ]. Moreover, the highest color and conductivity removal efficiency were given by the PSf/PVP 0.25 membrane.…”
Section: Resultsmentioning
confidence: 81%
“…In COD and TDS removal, the PSf/PVP 0.35 membrane had the highest removal efficiency. It indicated that the pore size affected the removal process, where it was previously confirmed that the PSf/PVP 0.35 membrane had the lowest porosity compared to other membranes [ 55 ]. Moreover, the highest color and conductivity removal efficiency were given by the PSf/PVP 0.25 membrane.…”
Section: Resultsmentioning
confidence: 81%
“…38,39 In membrane ltration, pore size is a critical factor in achieving ltration, rather than the specic weave. 40 For oil-water separation, the spacing of yarns is a design consideration, 41 with potential advantages associated with a more intricate weave that allows for distinct functionalization of the two sides of the fabric. 41,42 Therefore, the design of oleophobic fabrics may also require consideration of other properties specic to the end application of the textile.…”
Section: Discussionmentioning
confidence: 99%